Innovative smart biosensors for cancer theranostics: A new frontier in detection, diagnosis, and beyond - Archna Dhasmana; Ayushi Santhanam; Khushi Dhasmana; Sumira Malik; Subham Preetam (Cancer Treatment and Research Communications)
Cancer is still a major health concern worldwide, requiring ongoing improvements in methods of diagnosis and treatment. During the past decade, smart biosensors have become essential instruments in cancer theranostics, improving diagnosis accuracy, tracking treatment efficacy, and customizing patient care. This review thoroughly investigates how smart biosensors have revolutionized the field of cancer. The potential of major technical advancements, such as wearable technology, microfluidic platforms, and sensors based on nanomaterials to identify cancer biomarkers with high sensitivity and specificity is investigated. A detailed discussion is held regarding clinical applications that include early diagnosis, real-time monitoring of therapy responses, and support for personalized medicine techniques. Future directions targeted at optimizing the therapeutic utility of smart biosensors in oncology are also examined, along with issues pertaining to regulatory routes and clinical translation hurdles. This study highlights the potential of smart biosensors to transform cancer treatment, bringing in a new era of precision medicine and better patient outcomes by combining insights from multiple viewpoints.